2015
DOI: 10.1590/1678-4162-8148
|View full text |Cite
|
Sign up to set email alerts
|

Avaliações clínica, ecográfica e anatomofisiológica do alotransplante parcial de vesícula urinária com células-tronco mesenquimais alogênicas derivadas do tecido adiposo em coelhos

Abstract: Avaliações clínica, ecográfica e anatomofisiológica do alotransplante parcial de vesícula urinária com células-tronco mesenquimais alogênicas derivadas do tecido adiposo em coelhos [Clinical, sonographic, anatomic

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 14 publications
2
4
0
Order By: Relevance
“…Haematuria happened 24 hours after surgery, but no on the subsequent days. As a verified by previous studies (Pinto Filho et al 2015Filho et al , 2016, it is a common finding during early postoperative of urinary bladder surgery. WBC showed no significant differences between pre-and postoperative period and between groups; during this time, leukocyte counting was in the normal range for the specie.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Haematuria happened 24 hours after surgery, but no on the subsequent days. As a verified by previous studies (Pinto Filho et al 2015Filho et al , 2016, it is a common finding during early postoperative of urinary bladder surgery. WBC showed no significant differences between pre-and postoperative period and between groups; during this time, leukocyte counting was in the normal range for the specie.…”
Section: Discussionsupporting
confidence: 67%
“…Cyclosporine, used in the CGcy, is preferred by some researchers as an immunosuppressive agent in transplanted animals (Teixeira et al 2007, Chaves et al 2008). Pinto Filho et al (2015) used cyclosporine to prevent rejection for 30 days after partial cystectomy surgery in rabbits and found no signs of implant rejection in all treated animals. Chaves et al (2008) verified that cyclosporine prolonged survival of skin grafts in rabbits.…”
Section: Discussionmentioning
confidence: 99%
“…Several authors have reported a simple continuous pattern, the same as we used to suture the graft to the bladder wall and had no urine extravasation (ALBRECHT et al, 2006;OLIVEIRA et al, 2008;PINTO FILHO et al, 2015). However, IIJIMA et al ( 2007) observed uroperitoneum followed by death with the same suture pattern.…”
Section: Rodrigues Et Almentioning
confidence: 80%
“…No animal had surgical wound complications, that is no local sensitivity, hyperthermia, suture dehiscence, behavior changes or any signs of infection or graft rejection as also seen by PINTO FILHO et al (2015) in rabbits underwent bladder allograft. This fact can be related to an adequate surgical technique and to the tunica albuginea graft satisfactory consolidation with the receptor organ.…”
Section: Rodrigues Et Almentioning
confidence: 96%
“…Pinto Filho., et al [21] reported good recovery of surgical wound with no local sensitivity, no hyperthermia, or suture dehiscence in animals. During necropsy, no signs of infection or graft rejection were recorded indicating good application of surgical technique and adequate use of biomaterial as graft.…”
Section: Resultsmentioning
confidence: 97%